Metallogenic Theory and Exploration Technology of Multi-Arc-Basin-Terrane Collision Orogeny in "Sanjiang" Region, Southwest China - Li, Wenchang (The China Geological Survey Series, 2023)
This open access book presents a new structural model of "multi-arc-basin-terrane system" based on the in-depth research of the Nujiang-Lancangjiang-Jinshajiang region, especially several Paleo-Tethys ophiolitic mélange belts and sets of arc-basin systems, and a new orogenic model of "The Hengduan shan Mountains" based on penetrated research on spatial-temporal framework and orogenic models of different orogenic belts under large-scale strike-slip-shear-nappe structures evolution. The authors paid special attention on the coupling relation between orogeny and metallogenesis. The metallogenesis and dynamic process are probed under the crust-mantle interaction and material-energy exchange-transmission background and the tectonic units evolution. The ore genesis and distribution of deposits have been thoroughly analyzed, and the metallogenic theories of "multi-arc-basin-terrane" and "intracontinental tectonic transformation" in the Nujiang-Lancangjiang-Jinshajiang region have been carried out. This book also illustrates how to explore metallic deposits in the Nujiang-Lancangjiang-Jinshajiang region by using the metallogenic regulations. Meanwhile, this book has high reference value for researchers working in the fields of basic geology, environmental geology, and energy geology.